Different Classes of Ribonucleic Acid Isolated from Lymphocytic Choriomeningitis Virus - Pedersen, Ib Rode (1973)
Purified preparations of lymphocytic choriomeningitis virus (LCM virus) contain three classes of RNA. The previously described 18s, 23s, 28s, and 31s RNAs, where the 23s and 31s RNAs are viral-specific, and the 18s and 28s RNAs probably are host RNAs incorporated in the virion. Now, 4s, 5s, and 5.5s RNAs can be isolated as well. Thus five RNAs which migrate by acrylamide gel electrophoresis as ribosome-derived RNA can be isolated from purified LCM virus. This observation further supports the reports that arenaviruses may contain ribosomes. The ribosome-derived RNA can be synthesized both before and after the virus infection. The viral 23s could be a hydrogen-bonded complex forming the 31s RNA, or it could be contained in defective interfering LCM virus particles; these possibilities are examined.